Extending the Library of Light‐Dependent Protochlorophyllide Oxidoreductases and their Solvent Tolerance, Stability in Light and Cofactor Flexibility. Issue 16 (28th July 2020) - Schmermund, Luca; Bierbaumer, Sarah; Schein, Viktor K.; Winkler, Christoph K.; Kara, Selin; Kroutil, Wolfgang
Abstract: Biocatalysis is increasingly used in combination with light to develop new and more sustainable synthetic methods. Thereby, mostly a chemical photocatalyst harvesting the light energy is combined with an established enzymatic reaction, thus the biocatalyst itself does not require the light for its specific reaction. Here we expand the library of an enzyme which requires light for its natural reaction, namely the light‐dependent protochlorophyllide oxidoreductase (LPOR). This enzyme catalyzes the NADPH‐dependent reduction of a C=C in a N ‐heterocycle. Out of five LPORs identified by sequence search, four were found to be well expressible in E. coli and active. Investigating the light intensity, which is an important parameter describing energy input and subsequently may enable fast reaction, it turned out that the four LPORs can stand the maximum light intensity reachable with the equipment used (1450 μmol photons m −2  s −1 ). However, the natural substrate and product were degraded at these conditions, allowing only 15 % of the maximum input (211 μmol photons m −2  s −1 ). Furthermore, the LPORs accepted seven different water miscible solvents with a solvent content of up to 20 % v/v and were active at a pH from 6 to 10. While all LPORs known to date are exclusively NADPH dependent, two LPORs identified here were active also with NADH. The cofactor selectivity could be pinned to three amino acid residues, which interestingly do not directly bind to the cofactor. Abstract : Biotransformations : The library of light‐dependent protochlorophyllide oxidoreductases (LPORs) was extended and characterized towards solvent tolerance, possible light intensity, pH optimum and cofactor flexibility. NADH dependent LPORs were identified for the first time.